A Quality control study on Avon Philippines, Inc. - Catbagan, Jennifer P.; Garcia, Florimae B.; Ligon, Ronald Anthony V.; Lim, Geoffrey B. (College of Engineering, 1998)
The company under study is AVON Philippines, Inc. which is a world class manufacturer of beauty products. The group focused on the study on the quality of lipstick production. Documentation of the process is done through interviews, review of related literature, observations and data gathering. It was found out that the main problem in the production is on the occurrence of defects on surface finish. The group traced the causes and generated possible solutions to decrease, if not eliminate the occurrence of these defects. This study provided the company with a Design of Experiment to be able to implement the proposed alternatives.